Three/Four-leg Inverter Current Control Based on Generalized Symmetrical Components - Liberado, E. V. [UNESP]; Alonso, A. M. S. [UNESP]; Marafao, F. P. [UNESP]; Pomilio, J. A.; Tedeschi, E.; Guerreiro, J. F.; IEEE (Ieee, 2018)
Considering a scenario of high penetration of voltage source inverters in distribution grids, on which the number of conductors is variable, this paper proposes a current control approach for three- or four-leg inverters based on the generalized symmetrical components decomposition of non-sinusoidal signals. The approach is an alternative to d - q and alpha - beta transformation based approaches and allows to model and design the control system directly in the (the frame. Simulation results of three and four-leg inverters operating as multifunctional interfaces of distributed energy resources are presented, as well as comparative results of the proposed approach and other abc frame-based approaches to control four-leg inverters.
Keywords: control of power converters; switching power interface; distributed energy resources; multifunctional power converter; generalized symmetrical components